Effect of Angiotensin Receptor Blockers on Renal Function Biomarkers in Early-Stage Diabetic Nephropathy - Shabana Aziz, Sibgha Usman, Farooq Sultan, Irfan Ahmad, Syed Azhar Hussain Zaidi, Muhammad Usman, (International Journal of Pharmacy Research & Technology (IJPRT), 2025)
Angiotensin receptor blockers (ARBs) are established agents in slowing diabetic nephropathyprogression; however, their impact on emerging biomarkers in early-stage disease remains underexplored. In this randomized experimental trial, 140 type 2 diabetic patients